Preparation process of anti-erosion high-purity zirconium oxide product
Through a multi-stage preparation process, combined with the mixed grinding, spray granulation and thermal isostatic pressure treatment of horizontal sand mills, the corrosion problem of refractory materials for steelmaking furnaces in high temperature and high pressure environments is solved, and high-purity zirconia products with high density and corrosion resistance are prepared, which extends the service life of the steelmaking furnace and reduces production costs.
Patent Information
- Application Number
- CN202510067590.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Refractories used in steelmaking furnaces are susceptible to slag corrosion, thermal stress damage and high-speed airflow erosion in high temperature and high pressure environments, resulting in serious corrosion damage and affecting the service life and production efficiency of steelmaking furnaces.
A multi-stage preparation process is adopted, including pretreatment, granulation, molding, presintering, high-temperature sintering and post-treatment. Through mixed grinding of horizontal sand mills, spray granulation, bonding of thermosetting phenolic resins and the use of composite lubricants, the uniform mixing of high-purity zirconia powder and additives and the uniform particle size of particles are ensured, and the denseness and corrosion resistance of the product are further improved through thermal isostatic pressure treatment.
The prepared corrosion-resistant high-purity zirconia products have high density and significantly improved corrosion resistance, which can more effectively resist slag corrosion, thermal stress damage and high-speed airflow erosion, extend the service life of steelmaking furnaces and reduce production costs.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of refractory materials, and in particular relates to a preparation process of corrosion-resistant high-purity zirconium oxide products. Background Art
[0002] The life of a steelmaking furnace mainly depends on the refractory material of the working layer. The safety layer of a steelmaking furnace mainly supports the working layer and can replace the working layer in the event of an unexpected failure of the working layer, and maintain short-term safe operation until the furnace is shut down for maintenance. The thermal insulation layer of a steelmaking furnace mainly plays the role of thermal insulation of the entire furnace body, ensuring that the outer shell temperature of the furnace body is within a safe temperature range and reducing heat dissipation losses on the outer surface of the furnace body.
[0003] Due to the complex working conditions inside the steelmaking furnace, the refractory bricks in the working layer serve in a high temperature and high pressure environment for a long time, and are subjected to erosion by high temperature slag, scouring by airflow, and severe temperature fluctuations, and are also directly subjected to flame scouring in some parts.
[0004] Therefore, the penetration erosion of slag, the destruction of thermal stress and the erosion of slag and high-speed airflow are the main reasons for the erosion of steelmaking refractory materials. Therefore, the refractory materials used in steelmaking furnaces, especially the refractory materials used in the working layer, need to improve their thermal shock resistance and pressure resistance.
[0005] Therefore, the development of high-performance erosion-resistant refractory materials is of great significance for increasing the service life of steelmaking furnaces, reducing production costs, and improving steel production efficiency. Due to its unique properties, high-purity zirconia products have shown great potential in solving the erosion problem of refractory materials in steelmaking furnaces. Summary of the invention
[0006] Purpose of the invention: In order to overcome the above shortcomings, the purpose of the present invention is to provide a preparation process for corrosion-resistant high-purity zirconia products. The process has a reasonable design and starts from raw material pretreatment, through granulation, compression molding, pre-sintering, high-temperature sintering and post-treatment, etc., to gradually optimize the performance and structure of the material, and prepare high-purity zirconia products with high corrosion resistance, which has broad application prospects.
[0007] The objective of the present invention is achieved through the following technical solutions: A preparation process of a corrosion-resistant high-purity zirconium oxide product comprises the following steps: S1 pretreatment: high-purity zirconium oxide powder and composite additives are placed in a horizontal sand mill, and mixed and ground with Φ2mm zirconium oxide balls as grinding media at a medium-material ratio of 5:1, the grinding time is 18-24 hours, and the rotation speed is 200-300rpm; after the mixed grinding is completed, it is dried at 90-110°C for 3-4 hours to obtain a pretreated mixed raw material; S2 granulation: Add binder and composite lubricant to the pretreated mixed raw materials, and then granulate them in a spray granulation tower. The particle size of the mixed raw materials after granulation is controlled at 40~60μm; S3 compression molding: Put the granulated mixed raw materials into a mold and perform compression molding on a press. The molding pressure is controlled at 200-300 MPa and the holding time is 5-8 minutes to obtain a green body. S4 pre-sintering: Place the green body in a high-temperature furnace for pre-sintering, control the heating rate at 5 ~ 10 ° C / min, control the pre-sintering temperature at 1300 ~ 1400 ° C, and keep the temperature for 3 ~ 4 h; S5 high temperature sintering: the pre-sintered green body is sintered at high temperature in a high temperature sintering furnace, the heating rate is controlled at 5-10℃ / min, the sintering temperature is controlled at 1700-1800℃, and the holding time is 6-8h to obtain zirconium oxide products; S6 post-treatment: Place the zirconium oxide product in a hot isostatic pressing device and process it at 1500~1700℃ and 100~200MPa for 2~4h to obtain corrosion-resistant high-purity zirconium oxide products.
[0008] The preparation process of the corrosion-resistant high-purity zirconium oxide product of the present invention has reasonable step design. The high-purity zirconium oxide powder and the composite additive are fully and evenly mixed by mixing and grinding for a long time in a horizontal sand mill, which is conducive to the additive playing a role in the subsequent sintering process and improving the uniformity and performance stability of the material. Then, a spray granulation tower is used for granulation, which can accurately control the particle size within the appropriate range of 40 to 60 μm, ensure the fluidity and filling property of the material during subsequent compression molding, and is conducive to obtaining a green body with high dimensional accuracy and uniform structure. Then, the pre-sintering and high-temperature sintering processes respectively control the heating rate at 5 to 10 ° C / min and the appropriate sintering temperature and holding time, which helps to gradually remove impurities and gases in the green body, promote crystal growth and densification, and improve the density and performance of the product. Among them, pre-sintering can make the green body initially formed and exclude some binder decomposition products, etc., creating better conditions for high-temperature sintering, and high-temperature sintering further improves the density and strength of the material.
[0009] The present invention also performs a post-treatment of hot isostatic pressing after sintering, which can further eliminate tiny defects and pores inside the product under high temperature and high pressure, significantly improve the density and corrosion resistance of the zirconia product, and make the performance of the zirconia product more excellent and stable.
[0010] Furthermore, in the above-mentioned preparation process of the corrosion-resistant high-purity zirconium oxide product, the purity of the high-purity zirconium oxide powder is ≥99.99%, and the particle size is 0.3~1μm.
[0011] Zirconia powder with a purity of ≥99.9% and a particle size of 0.3~1μm is selected as the basic raw material. Higher purity can reduce the presence of impurities, thereby ensuring the chemical stability of zirconia products and reducing the penetration and erosion of slag. Smaller and more uniform particle size helps to improve the sintering performance and density of the product, thereby reducing the channels for slag penetration and enhancing the ability to resist penetration and erosion. At the same time, uniform particle size distribution can make zirconia products expand and contract more evenly when heated, reduce the generation of thermal stress, and improve the ability to resist thermal stress damage.
[0012] Furthermore, in the above-mentioned preparation process of the corrosion-resistant high-purity zirconium oxide product, the addition amount of the composite additive is 5-15% of the mass of the high-purity zirconium oxide powder; the composite additive includes yttrium oxide, cerium oxide, zirconium carbide, and zirconium nitride.
[0013] Yttrium oxide and cerium oxide have a synergistic effect in stabilizing the crystal phase structure of zirconium oxide. The composite stabilizer system formed by them can more effectively inhibit the phase change of zirconium oxide at high temperature, reduce the volume change and internal stress caused by the phase change, and thus improve the product's resistance to thermal stress damage. At the same time, the introduction of second-phase additives zirconium carbide and zirconium nitride with high temperature stability and high strength has high hardness, high melting point and good chemical stability. It can play a role of dispersion strengthening in zirconium oxide products, improve the hardness and strength of the products, and enhance their ability to resist slag and high-speed airflow erosion. At the same time, these reinforcing phases can also fill the pores inside the product, further improve the density, reduce the penetration channel of slag, and improve the ability to resist penetration erosion.
[0014] Furthermore, in the preparation process of the above-mentioned corrosion-resistant high-purity zirconia products, the addition amount of yttrium oxide is 2~5% of the mass of high-purity zirconia powder; the addition amount of cerium oxide is 1~3% of the mass of high-purity zirconia powder; the addition amount of zirconium carbide is 1~4% of the mass of high-purity zirconia powder; and the addition amount of zirconium nitride is 1~3% of the mass of high-purity zirconia powder.
[0015] Adding yttrium oxide, cerium oxide, zirconium carbide and zirconium nitride in the above proportion can work together well to improve the comprehensive performance of zirconium oxide products.
[0016] Furthermore, in the above-mentioned preparation process of the corrosion-resistant high-purity zirconium oxide product, the added amount of the binder is 3-8% of the mass of the high-purity zirconium oxide powder; and the binder is a thermosetting phenolic resin.
[0017] Thermosetting phenolic resin can undergo cross-linking reaction under heating and curing agent to form a three-dimensional network structure with good bonding performance and high strength. It can effectively bond the mixed raw material particles together and maintain the shape and structural stability of the green body during the subsequent molding and sintering process. In addition, its decomposition temperature is relatively high, and it will not decompose prematurely during the granulation and pre-sintering process, which can ensure the bonding effect.
[0018] Preferably, the binder is 2123 phenolic resin.
[0019] Furthermore, in the above-mentioned preparation process of corrosion-resistant high-purity zirconium oxide products, the addition amount of the composite lubricant is 1-3% of the mass of the high-purity zirconium oxide powder; the composite lubricant includes stearic acid and paraffin.
[0020] The lubricant is a combination of stearic acid and paraffin. Stearic acid has good lubricity and demoulding properties, which can reduce the friction between the material and the mold, ensure the smoothness of the compression molding process, make the surface of the blank smooth, and reduce defects such as cracks. Paraffin has a low melting point and good plasticity, which can further improve the fluidity of the material during the molding process, and play a synergistic role with stearic acid to improve the lubrication effect.
[0021] Furthermore, in the above-mentioned preparation process of corrosion-resistant high-purity zirconium oxide products, the added amount of stearic acid is 0-2% of the mass of high-purity zirconium oxide powder; and the added amount of paraffin is 0-1% of the mass of high-purity zirconium oxide powder.
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation process of the corrosion-resistant high-purity zirconium oxide product disclosed in the present invention is reasonably designed. In the pretreatment step, a horizontal sand mill is used to mix and grind with a specific medium-material ratio, suitable grinding time and rotation speed. Compared with some simple stirring and mixing processes, this grinding method can make the high-purity zirconium oxide powder and the composite additive more fully and evenly mixed, ensuring the uniform distribution of the additive in the zirconium oxide matrix, which is conducive to giving full play to the synergistic effect of each additive in the subsequent sintering process and effectively improving the performance of the material; high-purity zirconium oxide powder with a purity of ≥99.99% is selected as the basic raw material, and its particle size is controlled within the range of 0.3-1μm. Compared with the process using raw materials with lower purity or wider particle size distribution, it can better ensure the purity and performance consistency of the product, reduce the influence of impurities on material performance, improve the activity and sintering performance of the raw materials, and make the zirconium oxide product more uniform and dense in microstructure, thereby improving the corrosion resistance; (2) The preparation process of the corrosion-resistant high-purity zirconium oxide product disclosed in the present invention uses a spray granulation tower to perform granulation, and accurately controls the particle size of the mixed raw material particles after granulation to be 40-60 μm. Compared with the traditional granulation method, this process can more accurately control the size and shape of the particles. The particles with uniform particle size have better fluidity and filling properties during the compression molding process, which can make the density of the green body more uniform and reduce the generation of internal defects, laying a foundation for subsequent sintering and performance improvement; (3) The preparation process of the corrosion-resistant high-purity zirconia product disclosed in the present invention adopts a multi-stage sintering process combining pre-sintering and high-temperature sintering, and strictly controls the heating rate, sintering temperature and holding time. Compared with some processes with a single sintering stage or imprecise sintering parameter control, this multi-stage sintering process can better control the microstructure and performance of the product, reduce the generation of defects such as pores and cracks, and improve the corrosion resistance and mechanical properties of the product; finally, the zirconia product is post-treated under high temperature and high pressure conditions using hot isostatic pressing equipment. This post-treatment method can apply uniform pressure to the zirconia product, so that the pores and defects inside the zirconia product are effectively eliminated and closed under high temperature and high pressure; (4) The preparation process of the corrosion-resistant high-purity zirconia product proposed in the present invention includes adding a composite additive during pretreatment. The design of the composite additive can work well together to improve the comprehensive performance of zirconia. A binder phenolic resin and a composite lubricant are added during the granulation process. The phenolic resin can form a good bond between the raw material particles to ensure the shape stability of the blank during the molding and sintering processes. The composite lubricant can reduce the friction between the material and the mold and improve the processing performance of the material. Compared with using only a single additive, this design can better ensure the quality and performance of the blank, reduce defects such as cracks and delamination during the molding process, and improve the overall quality of the zirconia product. DETAILED DESCRIPTION
[0023] The following examples 1 and 2 are combined with specific experimental data to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The following Examples 1 and 2 provide a preparation process for a corrosion-resistant high-purity zirconium oxide product.
[0024] Example 1 The preparation process of the corrosion-resistant high-purity zirconium oxide product of Example 1 comprises the following steps: S1 pretreatment: high-purity zirconium oxide powder (purity ≥ 99.99%, particle size 0.3 ~ 1μm), composite additives (yttrium oxide added in an amount of 3% of the mass of high-purity zirconium oxide powder, cerium oxide added in an amount of 2% of the mass of high-purity zirconium oxide powder, zirconium carbide added in an amount of 2% of the mass of high-purity zirconium oxide powder, zirconium nitride added in an amount of 1% of the mass of high-purity zirconium oxide powder) are placed in a horizontal sand mill, and mixed grinding is performed with Φ2mm zirconium oxide balls as grinding media and a medium-material ratio of 5:1. The grinding time is 24h and the rotation speed is 200rpm. After the mixed grinding is completed, it is dried at 100°C for 4h to obtain a pretreated mixed raw material; S2 granulation: Add binder 2123 phenolic resin (the addition amount is 5% of the mass of high-purity zirconium oxide powder) and composite lubricant (the addition amount of stearic acid is 1.5% of the mass of high-purity zirconium oxide powder, and the addition amount of paraffin is 0.5% of the mass of high-purity zirconium oxide powder) to the pretreated mixed raw materials, and then granulate in a spray granulation tower. The particle size of the mixed raw material particles after granulation is controlled at 40~60μm; S3 compression molding: the mixed raw materials after granulation are placed in a mold and compression molded on a press. The molding pressure is controlled at 250 MPa and the holding time is 6 minutes to obtain a green body; S4 pre-sintering: put the green body into a high temperature furnace for pre-sintering, the heating rate is controlled at 6℃ / min, the pre-sintering temperature is controlled at about 1350℃, and the holding time is 3 h; S5 high temperature sintering: the pre-sintered green body is sintered at high temperature in a high temperature sintering furnace, the heating rate is controlled at 8°C / min, the sintering temperature is controlled at about 1800°C, the holding time is 7h, and the zirconia product is obtained; S6 Post-treatment: Place the zirconium oxide product in a hot isostatic pressing device and process it at 1600° C. and 120 MPa for 3 hours to obtain the corrosion-resistant high-purity zirconium oxide product of Example 1.
[0025] Example 2 The preparation process of the corrosion-resistant high-purity zirconium oxide product of Example 2 comprises the following steps: S1 pretreatment: high-purity zirconium oxide powder (purity ≥ 99.99%, particle size 0.3 ~ 1μm), composite additives (yttrium oxide added in an amount of 4% of the mass of high-purity zirconium oxide powder, cerium oxide added in an amount of 1.5% of the mass of high-purity zirconium oxide powder, zirconium carbide added in an amount of 3% of the mass of high-purity zirconium oxide powder, zirconium nitride added in an amount of 1% of the mass of high-purity zirconium oxide powder) are placed in a horizontal sand mill, and mixed grinding is performed with Φ2mm zirconium oxide balls as grinding media and a medium-material ratio of 5:1. The grinding time is 24h and the rotation speed is 220rpm. After the mixed grinding is completed, it is dried at 100°C for 4h to obtain a pretreated mixed raw material; S2 granulation: Add binder 2123 phenolic resin (the addition amount is 5% of the mass of high-purity zirconium oxide powder) and composite lubricant (the addition amount of stearic acid is 2% of the mass of high-purity zirconium oxide powder, and the addition amount of paraffin is 0.5% of the mass of high-purity zirconium oxide powder) to the pretreated mixed raw materials, and then granulate in a spray granulation tower. The particle size of the mixed raw material particles after granulation is controlled to be 40~60μm; S3 compression molding: the mixed raw materials after granulation are placed in a mold and compression molded on a press. The molding pressure is controlled at 240 MPa and the holding time is 8 minutes to obtain a green body; S4 pre-sintering: put the green body into a high temperature furnace for pre-sintering, the heating rate is controlled at 5℃ / min, the pre-sintering temperature is controlled at about 1350℃, and the holding time is 3 h; S5 high temperature sintering: the pre-sintered green body is sintered at high temperature in a high temperature sintering furnace, the heating rate is controlled at 6°C / min, the sintering temperature is controlled at about 1800°C, the holding time is 7h, and the zirconia product is obtained; S6 Post-treatment: Place the zirconium oxide product in a hot isostatic pressing device and process it at 1550° C. and 130 MPa for 3 hours to obtain the corrosion-resistant high-purity zirconium oxide product of Example 2.
[0026] Effect verification: The performance of the zirconium oxide products obtained in the above Examples 1 and 2 was tested. The test results are shown in Table 1. The test standards are as follows: (1) The national standard (GB / T 2009-2000) is used to test the bulk density and apparent porosity.
[0027] (2) The national standard (GB / T 5072-2008) is used to test the compressive strength at room temperature.
[0028] (3) The national standard (GB / T 34218-2017) is used to test the high temperature compressive strength.
[0029] (4) The national standard (YB / T370-2016) is used to detect the load softening start temperature.
[0030] (5) The national standard (GB / T 30873-2014) is used to test thermal shock resistance.
[0031] (6) The industry standard JC / T 2138-2012 is used to test the acid corrosion resistance and alkali corrosion resistance (the acid corrosion rate is the weight reduction after immersion in 80℃, 3mol / L sulfuric acid for 100h, and the alkali corrosion rate is the weight reduction after immersion in 80℃, 6mol / L sulfuric acid for 100h).
[0032] Table 1 Performance test results performance Example 1 Example 2 <![CDATA[Bulk density (g / cm 3 ).]]> 5.81 5.92 Apparent porosity (%) 6.4 5.7 Room temperature compressive strength (MPa) 568 585 1350℃ high temperature compressive strength (MPa) 113.6 120.4 Load softening starting temperature, 0.2MPa×0.6%, ℃ ≥1750 ≥1750 Thermal shock stability, 1100℃ water cooling, ≥30 ≥35 Acid corrosion rate (%) 1.1 1.0 Alkali solution corrosion rate (%) 2.0 1.8 In summary: the present invention provides an effective preparation process for corrosion-resistant high-purity zirconia products, starting from raw material pretreatment, through the optimization design of multiple links such as granulation, compression molding, pre-sintering, high-temperature sintering and post-treatment, to prepare zirconia products with high density and high corrosion resistance.
[0033] The present invention has many specific application paths, and the above is only a preferred embodiment of the present invention. It should be pointed out that the above embodiments are only used to illustrate the present invention, and are not used to limit the protection scope of the present invention. For those of ordinary skill in the art, several improvements can be made without departing from the principle of the present invention, and these improvements should also be regarded as the protection scope of the present invention.
Claims
1. A process for preparing a corrosion-resistant high-purity zirconium oxide product, characterized in that: The steps include: S1 pretreatment: high-purity zirconium oxide powder and composite additives are placed in a horizontal sand mill, and mixed and ground with Φ2mm zirconium oxide balls as grinding media at a medium-material ratio of 5:1, the grinding time is 18-24 hours, and the rotation speed is 200-300rpm; after the mixed grinding is completed, it is dried at 90-110°C for 3-4 hours to obtain a pretreated mixed raw material; S2 granulation: Add binder and composite lubricant to the pretreated mixed raw materials, and then granulate them in a spray granulation tower. The particle size of the mixed raw materials after granulation is controlled at 40~60μm; S3 compression molding: Put the granulated mixed raw materials into a mold and perform compression molding on a press. The molding pressure is controlled at 200-300 MPa and the holding time is 5-8 minutes to obtain a green body. S4 pre-sintering: Place the green body in a high-temperature furnace for pre-sintering, control the heating rate at 5 ~ 10 ° C / min, control the pre-sintering temperature at 1300 ~ 1400 ° C, and keep the temperature for 3 ~ 4 h; S5 high temperature sintering: the pre-sintered green body is sintered at high temperature in a high temperature sintering furnace, the heating rate is controlled at 5-10℃ / min, the sintering temperature is controlled at 1700-1800℃, and the holding time is 6-8h to obtain zirconium oxide products; S6 post-treatment: Place the zirconium oxide product in a hot isostatic pressing device and process it at 1500~1700℃ and 100~200MPa for 2~4h to obtain corrosion-resistant high-purity zirconium oxide products.
2. The process for preparing the corrosion-resistant high-purity zirconium oxide product according to claim 1, characterized in that: The purity of the high-purity zirconium oxide powder is ≥99.99%, and the particle size is 0.3~1μm.
3. The preparation process of the corrosion-resistant high-purity zirconium oxide product according to claim 1, characterized in that: The addition amount of the composite additive is 5-15% of the mass of the high-purity zirconium oxide powder; the composite additive includes yttrium oxide, cerium oxide, zirconium carbide and zirconium nitride.
4. The process for preparing the corrosion-resistant high-purity zirconium oxide product according to claim 3, characterized in that: The added amount of yttrium oxide is 2-5% of the mass of high-purity zirconium oxide powder; the added amount of cerium oxide is 1-3% of the mass of high-purity zirconium oxide powder; the added amount of zirconium carbide is 1-4% of the mass of high-purity zirconium oxide powder; and the added amount of zirconium nitride is 1-3% of the mass of high-purity zirconium oxide powder.
5. The process for preparing the corrosion-resistant high-purity zirconium oxide product according to claim 1, characterized in that: The added amount of the binder is 3-8% of the mass of the high-purity zirconium oxide powder; the binder is a thermosetting phenolic resin.
6. The process for preparing the corrosion-resistant high-purity zirconium oxide product according to claim 1, characterized in that: The addition amount of the composite lubricant is 1-3% of the mass of the high-purity zirconium oxide powder; the composite lubricant includes stearic acid and paraffin.
7. The process for preparing the corrosion-resistant high-purity zirconium oxide product according to claim 6, characterized in that: The added amount of stearic acid is 0-2% of the mass of the high-purity zirconium oxide powder; the added amount of paraffin is 0-1% of the mass of the high-purity zirconium oxide powder.
Citation Information
Patent Citations
Zirconia metering nozzle manufacturing method
CN102249704A
Sintered body and cutting tool containing same
CN107922274A
Zirconia ceramic material and preparation method thereof, and zirconia ceramic structure member
CN110655401A
Nozzle as well as preparation method and application thereof
CN113698202A
Cerium oxide / yttrium oxide composite stabilized zirconium oxide grinding medium and preparation method thereof
CN119038989A